European perspectives on John Updike - Mazzeno, Laurence W.; Norton, Sue, 1964- (European studies in North American literature and culture., 2018)
From his first book publication in 1958, the American writer John Updike attracted an international readership. His books have been translated into twenty-three languages, and he has always had a strong following in the United Kingdom and in Europe. Although Updike died in 2009, interest in his work remains strong among European scholars. No recent volume, however, collects diverse European views on Updike's oeuvre. The current book fills that void, presenting essays that perceive Updike's renditions of America through the eyes of scholar/readers from both Western and Eastern Europe--back cover.